Communication theory teaching and the challenges of de-westernization of communication theories - Muzayin Nazaruddin; Ida Nuraini Dewi Kodrat Ningsih (Department of Communications, Universitas Islam Indonesia, 2018)
Teaching communication theory in Indonesia and another non-Western countries generally deals with two challenges, namely Western perspective biases and negative perception of students who used to look at the course as complicated and boring. The paper offers teaching strategy for the communication theory course emphasizing contextualization as the core learning message, culturally responsive as the teaching approach, and student centred as the learning method. Students learn to relate the learning process with their everyday experience, so that they could develop meaning or function of the learning process. It would increase students’ motivation, involvement, and achievement. It would also be an important point to contextualize communication theory with empirical context, as contextualization is an important process of de-westernization of communication theories. Thus, the communication theory teaching is an initial step to de-westernize communication theory, which has a simple role: to criticize the relevance of established communication theories with local context.